Application Of Machine Vision On Solder Joint Inspection Using Orthogonal And Oblique Views - Ong , Teng Yeow (2010)

(untitled)
Machine vision has been widely deployed in many industrial applications. However, the use of machine vision to perform solder joint inspection of electronic assembly has yet to reach the desired maturity level. Solder joint surfaces are minute, curved and the shapes tend to vary greatly with the soldering conditions. These characteristics have posted a challenging task to develop an effective machine vision with acceptable level of classification accuracy. This research aims to investigate a new methodology of inspecting solder joint through analysis of the combined image from two viewing directions; one from orthogonal view while the other from oblique view. The concept based on the physics of surface tension, contact angle and slant angle of solder joint fillet.